Filmowa franczyza. Od tematu do widowiska telewizyjnego (na podstawie cyklu „Prawdziwe Historie”) - Otto , Wojciech (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2019)
The TV series True Stories (Prawdziwe Historie) is an example of contemporary commercial cinema. It is located on the border of documentary film and an attractive version of fictional cinema. In specific circumstances, it can be treated as a commercial product, but not only in the sense of film production and distribution, but more broadly, as a recognisable brand on the domestic cinema market, containing all the elements of industry know-how, as well as significant and commonly seen features of a film style that guarantees both turnout and financial success. In a sense, therefore, this phenomenon can be considered in terms of a film franchise which offers creators, most often beginners, a proven business patent in the form of a coherent television series, but also giving the possibility of a safe feature debut and the space for creative exploration.